TRANSITIONS IN IRISH MISCELLANIES BETWEEN 1923 AND 1940: THE IRISH STATESMAN AND THE BELL - Ballin, Malcolm (International Journal of English Studies, 2002)
Between 1923 and 1940 a variety of political and cultural events took place in Ireland, including the formation of the Free State, the establishment of the 1937 constitution by Eamon de Valera, and the adoption of a policy of neutrality in the Second World War. The effects of these changes are traced in the processes of production of two related periodicals, The Irish Statesman (1923-30) and The Be11 (1940-54). The differences and similarities between the editors of these journals, George Russell (E) and Sean O’Faolain, are discussed in the context of the intellectual history of the period, as are the processes of influence and reaction between them. The historical evolution of the miscellany as a specific periodical genre is considered, together with its influence upon the form and content of these publications. It is argued that particular audiences were created for these periodicals in post revolutionary Ireland and that they were both able, in different ways, to exert a benign influence on the development of the new nation.